Validation of Ponseti method for clubfoot deformity correction - Kumar, Sanjiv; Singh, Sudhir; Kumar, Dharmendra; Mohammad, Farid; Rai, Tushar; Verma, Reetu (International Journal of Research in Medical Sciences, 2017)
Background: Idiopathic Congenital Talipes Equino-Varus (CTEV) is a complex deformity of foot that is difficult to treat. The goal of treatment is to gain a functional, pain free, plantigrade foot, with good mobility and without callosities. Currently, the most accepted and popular method is the Ponseti method which allows correction of all components of CTEV by manipulation and serial casting without any major surgical intervention. This prospective study was done in a tertiary care centre to statistically assess the efficacy of Ponseti method. Methods: We treated 150 children (210 feet) with idiopathic clubfoot deformity, using Ponseti technique. The severity of foot deformities were assessed by Pirani scoring system and were also recorded clinically, radiologically and podographically. The changes in the mean Catterall-Pirani scores at different follow ups were evaluated statistically. Results: The mean number of casts that were applied to obtain correction was 7.86 (range 5 to 11 casts). Percutaneous tendoachilles tenotomy was done in 70% of feet. All children were given foot abduction orthosis after the correction. The results were graded according to Ponseti and Smoley criteria. Good results were obtained in 83% of feet, acceptable results in 7% of feet and poor results in 10% of cases. Statistically significant correction was achieved in manipulation and casting stage which was maintained during bracing phase. The recurrences of the deformity were primarily due to poor compliance in the use of orthosis in post correction phase. Conclusion: The Ponseti method of correction is a safe and effective treatment for congenital idiopathic clubfoot and radically decreases the need for extensive corrective surgery. Non-compliance with orthotics is the main factor causing relapse of the deformity.